2020
DOI: 10.31410/limen.2020.39
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Covid-19 on Exchange Rate Volatility: An Econophysics Approach

Abstract: This paper aims to analyze the efficiency, in its weak form, between exchange rates, US-RMB, US-EUR, US-JPY, US-MYR, US-PHP, US-SGD, US-THB, US-CHF, US-GBP, in the period from July 1, 2019 to October 27, 2020. To perform this analysis, different approaches were undertaken to assess whether: (i) the impact of the global pandemic created long memories in international foreign exchange markets? The results of the exponents Detrended Fluctuation Analysis (DFA) show that the exchange rates US-THB (0.60), US-MYR (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, one of the most unexpected characteristics of the COVID-19 pandemic shock was the stability in the exchange rates, in spite of a global recession. Dias and Santos (2020) concluded that the exchange rate markets had persistence and long memories, while Park et al (2020) revealed more stability in the exchange rate worldwide throughout the first three months of the COVID-19 pandemic. Ilzetzki et al (2020) found that the rising G3 currencies' (dollar, euro and yen) stability over the COVID-19 pandemic shock was an acceleration of a long-term trend.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, one of the most unexpected characteristics of the COVID-19 pandemic shock was the stability in the exchange rates, in spite of a global recession. Dias and Santos (2020) concluded that the exchange rate markets had persistence and long memories, while Park et al (2020) revealed more stability in the exchange rate worldwide throughout the first three months of the COVID-19 pandemic. Ilzetzki et al (2020) found that the rising G3 currencies' (dollar, euro and yen) stability over the COVID-19 pandemic shock was an acceleration of a long-term trend.…”
Section: Literature Reviewmentioning
confidence: 99%